Effects of Recent Minimum Wage Policies in California and Nationwide: Initial Results from a Pre-specified Analysis Plan - David Neumark; Maysen Yen (Institute of Labor Economics (IZA), 2020)
Many U.S. cities have recently increased their minimum wages, especially in California. We report results from carrying out analyses of the impacts of these city minimum wages, as specified in a pre-analysis plan (PAP) that was registered on Open Science Framework prior to the release of data covering two years of minimum wage increases. In this working paper, we report results updating the data through 2018; our final paper will add another year of evidence on minimum wages. For employment effects, in our analysis of California cities we find a hint of negative employment effects, but the estimates are neither robust nor statistically strong. The analysis of local minimum wages nationally also provides some evidence of disemployment effects, although it is not statistically significant. For distributional effects, our city-specific analyses do not provide clear evidence one way or the other, except for evidence of increases in the shares poor or low-income in Santa Clara. In our panel data analyses of all California or national local minimum wages, there is evidence pointing to declines in the shares poor or low-income, although at least for California the data indicate that the shares poor or low-income were declining before local minimum wages took effect (or were increased). More definitive results await our next update.
Keywords: J23; J38; 330; minimum wage; employment; poverty; low-income